Changes in the International Distribution of Resources and Their Impact on U.S. Comparative Advantage - Bowen, Harry P. (The Review of Economics and Statistics, 1983)
T HE Heckscher-Ohlin (H-O) theory suggests international trade is determined by relative resource supplies among countries. Prior empirical research, such as work on the determinants of U.S. comparative advantage in a single year, has concentrated on the static predictions of H-O theory. However, H-O theory also suggests changes over time in resource supplies will alter trade structure. The present paper investigates this aspect of H-O theory. Particular emphasis is given to the role of world resource changes as an explanation of changes in U.S. trade and of the increased international competition in manufactured goods faced by the United States. Some recent studies have examined the relationship between changes in resource endowments and trade. Heller (1976) examined changes in the factor content of Japan's trade between 1958 and 1968 and found the observed patterns-consistent with changes in Japan's physical and human capital endowments. Stern and Maskus (1981) investigated changing factor input determinants of U.S. trade by estimating annual cross-section regressions over 1958-77. They suggested U.S. net exports made less direct use of unskilled labor over time. Further, analysis of the factor content of U.S. trade suggested increased U.S. abundance in physical capital relative to human capital between 1958 and 1971. Balassa (1979), using a 1970 crosssection of countries, concluded that physical and human capital accumulation largely explained changing patterns of comparative advantage in manufactures. Although these studies made important contributions, a number of issues remain concerning the relationship between resources and trade. Stern and Maskus, in listing directions for further research, cite first an examination of How and why endowments of physical capital, human capital and labor have changed within the U.S. and our major trading partners. This paper reports a substantial data effort which addresses this topic. Another important consideration is that the direct effect of resource endowment variation on trade has yet to be determined. Previously, inferences about the effect of resource endowments on trade have been based primarily on results from industry cross-section regressions. Authors of such work indirectly infer the effect of resource variation on trade by assuming the coefficients from such regressions reflect resource abundance. However, Leamer and Bowen (1981) recently demonstrated that signs of coefficients from such regressions need not reflect a country's true resource abundance. Thus, the usual negative coefficient for the capital-labor ratio in an analysis of U.S. trade cannot be used to infer the scarcity of capital and thus cannot be used to infer the effect of an increase in capital endowment on U.S. trade. Similarly, Balassa's procedure of first regressing, for each of a sample of countries, industry trade on input intensity and then using the estimated coefficients as the dependent variable in a cross-country regression on resources is an inappropriate method for inferring the effect of resources on trade. This paper advances consideration of these issues by investigating aspects of the relationship between resources and trade. Section II examines changing patterns of resource supply among thirty-four countries over 1963-75. Section III investigates whether these resource changes are associated with altered comparative advantage in manufactured goods. Section IV uses cross-country regressions to estimate the resource endowment, as opposed to factor input, determinants of U.S. manufacturing trade and thereby the direct effect of resource variation on U.S. trade. The Received for publication April 23, 1981. Revision accepted for publication November 30, 1982. * New York University. This paper is an outgrowth of research in Bowen (1980a) and of further work conducted at UCLA under a Ford Foundation grant directed by Edward E. Leamer. An earlier version was presented at the 1980 Southern Economic Association meetings in Washington, D.C. Comments by C. Michael Aho, Robert Baldwin, Edward Leamer, Joseph Pelzman, Leo Sveikauskas and an anonymous referee are gratefully acknowledged. The author remains responsible for errors.